Exploring physical activity engagement and barriers for asylum seekers in Australia coping with prolonged uncertainty and no right to work. (30th January 2017) - Hartley, Lisa; Fleay, Caroline; Tye, Marian E.
Abstract: This paper explores the engagement in physical activity as a potential coping strategy for asylum seekers living in the Australian community without the right to work and with prolonged uncertainty, and benefits or barriers to undertaking such activity. Semi‐structured in‐depth interviews were held with 29 asylum seekers who had arrived to Australia by boat and were living in the community in the cities of Perth, Sydney or Melbourne in July–October 2013 after their release from immigration detention. The ratio of the numbers of men and women interviewed (23 men and 6 women) was comparable to the ratio of men and women who came by boat to Australia seeking asylum in 2012–2013. Nine participants reported that they participated in physical activity as a coping strategy. Seven other participants were so worried about their future and their families that they did not have the mental or physical energy to engage in physical activity. A further six wanted to participate in physical activity but faced a number of barriers to doing so. The seven remaining participants were either not asked about their physical activity engagement because they focused their discussion on other challenges or did not elaborate on why they were not engaging in physical activity. The findings suggest that physical activity, coupled with other coping strategies, are important for some asylum seekers in trying to manage the distress of being denied the right to work and living with prolonged uncertainty. In addition, these findings highlight the critical barrier that government policy plays in disabling engagement in physical activity, which further compounds social exclusion. This includes the lack of welfare support provided, which hinders people's financial ability to access activities and support in the community.